Pakistan : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Pakistan's Poverty Reduction Strategy Paper (PRSP) Preparation Status Report. The formulation of the Interim PRSP (I-PRSP) was the first step in the direction of preparing a comprehensive national antipoverty strategy that encompasses the economic, structural, and social initiatives undertaken and planned to be taken over the medium term by the federal, provincial, and district governments for targeting the multidimensional nature of poverty and human development in Pakistan. The full PRSP would reflect an updated status of existing policy programs as well as new initiatives taken by the federal government since November 2001.